Infantile hemangioma / Chalazion. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2020)
Infantile hemangioma (IH) and chalazion are two very different conditions. However, they share a nodular appearance and vasodilation; these common features can sometimes give rise to differential diagnosis problems, especially when IH is deeply located.